A mechanistic study on the synthesis of branched functional polyethylene through reactive co‐polymer approach. (22nd January 2020) - Jandaghian, Mohammad Hossein; Ahmadjo, Saeid; Mortzavi, Seyed Mohammad Mahdi; Ahmadi, Mostafa
Abstract : The reactive co‐polymer approach is one of the most promising techniques for the synthesis of functional polyolefins. Following this concept, 1‐hexene and p‐ methylstyrene are co‐polymerized in the presence of a generic Brookhart‐type catalyst. The microstructures of the co‐polymers imply the tendency of p ‐methylstyrene co‐monomers to place at the end of the structural branches formed by the chain walking reaction. The molar masses of the co‐polymers decrease, not only at higher levels of co‐monomer but surprisingly by decreasing reaction temperature. A mechanism consisting of a highly stable η 3 metal–benzyl intermediate, which is quantitatively approved by density functional theory calculations, can delicately justify all the aforementioned observations. A series of the produced co‐polymers is selectively functionalized by maleic anhydride at the benzylic position of p ‐methylstyrene, under very mild reaction conditions. Such a reactive intermediate opens the path for the introduction of different types of functionalities in polyolefins. Namely, the grafted co‐polymers were further functionalized by a triazole ring, which provides a transient supramolecular network through intermolecular hydrogen bonding. Abstract : Following the reactive copolymer approach, 1‐hexene and p ‐methylstyrene are copolymerized in the presence of a generic Brookhart‐type catalyst. A reaction mechanism consisting of a highly stable η 3 metal–benzyl intermediate is proposed and confirmed by DFT calculations, to explain the dependence of the microstructure on the reaction conditions. Selected samples are functionalized by maleic anhydride, selectively at the benzylic positions of the p ‐methylstyrene units, and transient supramolecular bonds are incorporated through further functionalization by a triazole groups.